Olah Makan Ikan: Peningkatan Keterampilan Pengolahan Ikan Bagi Masyarakat Desa Sawarna - Komarudin, Didin; Lim, Jonathan; Sonia, Afnenda Gina; Azwar, Muhamad Rizky Azru; Arista, Elma; Cahyani, Kurnia Indah; Irdiansyah, Muhammad Farrel; Sajidah, Salsabila; Ridho, Fadhal Abiyu (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2024)
Sawarna Village has fisheries potential and natural beauty which makes it one of the famous tourist village destinations in Banten Province. The training activities carried out were aimed at diversifying processed fish products, namely making fish dim sum from fish as an effort to fulfill nutrition and increase community income in Sawarna Village. The PLA (Participatory Learning and Action) method was used during the training outreach activities for making fish dim sum. The training activity was attended by 11 residents of Sawarna Village. The results of the evaluation of the training outreach activities for making fish dimsum can be seen in the average pretest score of 72,7 and the posttest score of 89,1 regarding understanding of fish dim sum, starting from the meaning, how to make it, and its benefits. The evaluation results are used as evidence that the fish dim sum making training outreach activities can be carried out by the people of Sawarna Village. Fish dim sum making activities can be used as a business idea that can develop MSMEs (Micro, Small, and Medium Enterprises) in Sawarna Village. This processed fish dim sum can be part of a culinary tour in Sawarna Village which is famous for its beautiful beaches and seas.